Out of Africa: detrital zircon provenance of central Madagascar and Neoproterozoic terrane transfer across the Mozambique ocean - Fitzsimons, Ian; Hulscher, B. (John Wiley and Sons, 2005)
The Neoproterozoic East African Orogen reflects closure of the Mozambique Ocean and collision of the Congo and Dharwar cratons. This palaeogeographic change and its environmental consequences are poorly understood, but new detrital zircon ages from Madagascar and published data from elsewhere provide evidence for multiple ocean basins and two-stage collision. We propose that central Madagascar rifted from the Congo Craton and crossed a Palaeomozambique Ocean to collide with the Dharwar Craton at c. 700 Ma, opening a Neomozambique Ocean in its wake. Closure of the Neomozambique Ocean at c. 600 Ma juxtaposed the Congo and Dharwar cratons and resulted in prolonged collisional orogenesis concluding at c. 500 Ma.